CtIP forms a tetrameric dumbbell-shaped particle which bridges complex DNA end structures for double-strand break repair - Wilkinson,OJ; Martín-González,A; Kang,H; Northall,SJ; Wigley,DB; Moreno-Herrero,F; Dillingham,MS (eLife, 2019)
CtIP is involved in the resection of broken DNA during the S and G2 phases of the cell cycle for repair by recombination. Acting with the MRN complex, it plays a particularly important role in handling complex DNA end structures by localised nucleolytic processing of DNA termini in preparation for longer range resection. Here we show that human CtIP is a tetrameric protein adopting a dumbbell architecture in which DNA binding domains are connected by long coiled-coils. The protein complex binds two short DNA duplexes with high affinity and bridges DNA molecules in trans. DNA binding is potentiated by dephosphorylation and is not specific for DNA end structures per se. However, the affinity for linear DNA molecules is increased if the DNA terminates with complex structures including forked ssDNA overhangs and nucleoprotein conjugates. This work provides a biochemical and structural basis for the function of CtIP at complex DNA breaks.